Petrogenesis and Sr-Nd isotope data of the Chadegan metabasites, Sanandaj-Sirjan Zone, Iran - Akbari, K. (2016)
The metabasites of Chadegan belong to the Sanandaj-Sirjan Zone and include eclogite, garnet amphibolite and amphibolite that have been affected by several tectono-metamorphic events. These rocks were metamorphosed during subduction of Neo-Tethys ocean crust under Eurasia. Subsequent exhumation occurred by upwards-directed mass flow in a subduction channel during continental collision between the Afro-Arabian continent and the Iranian micro-continent. Trace element geochemistry and high total REE concentrations show that the protoliths of the studied metabasites have an E-MORB character and formed in an ocean ridge setting. Slightly positive initial epsilon Nd values (+1.5 to +3.8 at 190 Ma) agree with an origin of the parental magmas in a mantle source that did not undergo severe depletion events, whilst a large range of (87Sr/86Sr)i values (0.70690 to 0.71624) testifies for the strong influence of continental crustal fluids during regional metamorphism.